2019
DOI: 10.1111/aec.12804
|View full text |Cite
|
Sign up to set email alerts
|

Using a species distribution model to guide NSW surveys of the long‐footed potoroo (Potorous longipes)

Abstract: This is the author manuscript accepted for publication and has undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Finally, a few studies have tested the ability of SDMs to predict occurrence using other methods. For example, Wauchope‐Drumm et al (2020) compared the average predicted suitability scores for independent presences versus absences for a rare marsupial, finding that mean suitability was significantly higher for independent presences than absences. Likewise, Pinto et al (2016) found that predicted suitability was higher for observed flapper skate tracks (based on geolocator data) than for random tracks.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, a few studies have tested the ability of SDMs to predict occurrence using other methods. For example, Wauchope‐Drumm et al (2020) compared the average predicted suitability scores for independent presences versus absences for a rare marsupial, finding that mean suitability was significantly higher for independent presences than absences. Likewise, Pinto et al (2016) found that predicted suitability was higher for observed flapper skate tracks (based on geolocator data) than for random tracks.…”
Section: Resultsmentioning
confidence: 99%
“…This study is important in identifying the consequence of habitat change on the habitat suitability of the Timor friarbird. This information is the basic knowledge for effective decision-making for habitat conservation (Wauchope-drumm et al 2019;Chiatante et al 2019). This study aims to assess landscape factors that contribute to the habitat suitability of the Timor friarbird and to determine whether the western part of Timor Island is the optimum habitat for the species.…”
Section: Introductionmentioning
confidence: 99%